Pricing and financial sustainability of selected micro financial institutions (MFIs) in Bangladesh - Purni, Nahida Islam (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.